ACUTE TOXICITY, PHYTOCHEMICAL SCREENING, AND ANTIMICROBIAL INVESTIGATION OF AQUEOUS EXTRACT OF SODOM APPLE TREE (Calotropis procera Ait.F) LEAF OBTAINED WITHIN ANCHOR UNIVERSITY, LAGOS - Olatunde A Oseni; Hilda A Emmanuel-Akerele; Wuraola A Adebayo (University of Sultan Ageng Tirtayasa, 2021)
Calotropis procera is a species of flowering plant, in the family Apocynaceae, the investigation of Calotropis procera for its medicinal usefulness has not been fully documented in the literatures. This study was therefore aimed at investigating the antimicrobial activity, phytochemical screening and acute toxicity of Calotropis procera. The antimicrobial activity, phytochemical screening and acute toxicity of the leaf was carried out using standard methods for the analyses. The antimicrobial activity of Calotropis procera leaf extract for bacterial showed that Streptococcus pyogenes, Staphylococcus aureus, Escherichia coli and Aspergillus candideus were resistant to the plant extract, while Penicillum corylophilum showed susceptibility to the plant extract. The phytochemical screening showed the presence of flavonoids, saponins and reducing sugar in the aqueous leaf extract of the leaf, while alkaloids and phlobatannins were absent in the extract of Calotropis procera. The acute toxicity investigation showed that Calotropis procera concentration at 1424 mg/kg body weight resulted in scratching and shivering but was not toxic to cause death of the mice, while lower concentrations of 142, 352, and 712 mg/kg body weight did not cause any observable negative reactions. The plant of Calotropis procera therefore showed that the aqueous extract of the plant contained viable phytochemicals compounds, potent antimicrobial activity to some organisms while the studied concentrations for acute toxicity were observed to be safe.